PENERAPAN SUSTAINABILITY MANAGEMENT DAN IMPELEMENTASI DATA MINING DALAM PERCEPATAN MENCAPAI TARGET DAN TUJUAN PERUSAHAAN - Wijaya NG (Universitas Pasundan, 2025)
In this era of globalization, companies are faced with various challenges, such as climate change, resource scarcity, and demands from stakeholders to run a sustainable business. One of the efforts to overcome this problem is Sustainability Management. The purpose of this research is to determine the application of sustainability management to accelerate the achievement of PT company targets and objectives Anugerah Textile Labda This study used qualitative research methods. The data collection technique in this research is a literature study by exploring journals, books, sustainability reports, company policies and related operational data. The collected data was analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that the implementation of total sustainability management (TSM) at PT. Labda Anugerah Tekstil helps companies accelerate the achievement of company targets and goals. This success is based on the achievements achieved by PT. Labda Anugerah Tekstil over the last few years since this company was founded, one of which is achieving the OEKO-TEX Standard 100 certificate and being recorded in the MURI record as the pioneer of the first digital printing company in Indonesia to carry an eco-friendly or environmentally friendly concept. TSM in a company can be said to be successful if it obtains profits that meet or even exceed targets, all parties who act as stakeholders are actively involved, existing obstacles and challenges can be overcome and provide benefits or positive impacts for individuals and the environment.